Sublimasi Politik dalam Aksi Bela Islam 212 - Muhammad Ainun Najib (Department of Political Science - Universitas Sains Al-Qur’an, 2018)
In a certain point, the relationship between religion and state in Indonesia has never been separated from various problems. Political sublimation is a clear example that religious and political affairs in practise have not yet been completed and are predicted to grow in the future. The most recent example is the Action of Defend Islam 212, where if we analyze further, the political interests cannot be separated from it. This paper tries to examine the phenomenon in Jakarta as an example of political sublimation by putting non-political things, in this case religion, into a very politically laden thing. This paper concludes that every event that occurs can have political meaning and purpose. Therefore, a social phenomenon cannot only be seen from one side.